In silico molecular studies of Phosphinogold(I) thiocarbohydrate complexes: insights into multi-target anticancer mechanisms - Mohamed, Alkhair Adam Khalil; Asiamah, Isaac; Elamin, Ghazi; Darkwa, James; Adokoh, Christian K. (Frontiers in Chemistry, 2025)
Introduction:This study employed in silico methods to investigate the anticancer potential and mechanisms of twenty novel phosphinogold(I) thiocarbohydrate complexes.Methods:Molecular docking and Prime MM-GBSA screening of seventeen cancer-related protein targets, including Human Double Minute 2 protein (HDM2), DNA methyltransferase-1 (DNMT1), Protein Kinase B (AKT2), and Poly (ADP-ribose) polymerase 1 (PARP-1), were conducted. Molecular dynamics simulations were performed for complex 9.Results:Virtual screening revealed strong binding affinities for several complexes, often surpassing native ligands. All the complexes except 16, 18, and 19 exhibited strong binding affinity with one or two cancer protein targets compared to native ligands. Complex 9 emerged as the best candidate, demonstrating promising binding affinity particularly against AKT2 (–82.40 kcal/mol) and PARP-1 (–75.7 kcal/mol). Molecular dynamics simulations of complex 9 with PARP-1 and AKT2 revealed distinct binding profiles, with a more stable interaction with PARP-1, suggesting its potential for disrupting DNA repair mechanisms. Binuclear complexes generally exhibited higher affinities than mononuclear counterparts, particularly for DNMT1 and HDM2. Complex 13 demonstrated high in vitro activity against prostate, colon, and breast cancer cell lines (IC50 = 0.03, 0.25, and 0.07 μM respectively), collaborating with a significant interaction with Human Epidermal Growth Factor Receptor 2 (HER2) (–71.15 kcal/mol binding affinity) in silico. While acetylation decreased binding affinity; it enhanced cellular activity as reported in in vitro studies indicative of the need to balance lipophilicity and binding strength in future ligand design.Discussion:These findings provide valuable insights into multi-target anticancer mechanisms, with a particular emphasis on complex 9 as a potential PARP-1 inhibitor, and guide future optimization and experimental validation of these novel gold-based complexes. The stable interaction of complex 9 with PARP-1 highlights PARP-1 as a particularly promising therapeutic target. Binuclear complexes' superior affinities for DNMT1 and HDM2 suggest structural advantages for multi-target inhibition.Conclusion:The paradoxical effect of acetylation underscores the importance of balancing lipophilicity and binding strength in ligand design.